(untitled) (Plant Tissue Culture and Biotechnology, 2026)
An efficient in vitro micropropagation and ex vitro establishment protocol was developed for Colocasia esculenta cv. antiquorum L (BARI Mukhikachu-1). This protocol produced suckers from in vitro plantlets after hardening and the plant establishment stage. Shoot tips from the sprout of cormel were used as explants. MS medium supplemented with 8.0 mg/l BAP + 0.5 mg/l IBA produced the highest number of shoots, 4.88 shoots per explant, after 35 days of culture. The highest number of roots, 22 roots per plantlet, was found in ½MS + 0.5 mg/l IBA after 35 days of culture. Rooted plantlets were acclimatized for 14 days in potting media containing ash and cocopeat at a 1 : 1 ratio. Established plants were transferred to a plastic pot containing 50% soil + 50% compost for 60 days to promote further growth and development. Each plant produced an average of 5.83 suckers, which can be used separately as planting materials. This protocol can be used for the large-scale production of uniform planting materials. Plant Tissue Cult. & Biotech. 36(1): 209-219, 2026 (June)